STUDENTS' PERCEPTION: A DIDACTICAL STUDY ON THE IMPACT OF CASE-BASED LEARNING AND TEAMWORK ON TEFL METHODOLOGY OF ENGLISH EDUCATION MASTER PROGRAM(S2BE) - Yuliana, Yohanes Gatot Sutapa; Elisa, Henry; Nugraha, Bayu Dwi (Journal of English Educational Study (JEES), 2024)
This research explores students' perceptions of the evolving Case-Based â€œTeaching English as a Foreign Languageâ€ (TEFL) Methodology and Team Work to enhance learning outcomes. It investigates the integration of linguistic aspects and their alignment with practical applications. Employing qualitative Didactical Design Research (DDR), the study employs observation sheets, interview guides, and documentation as research tools. DDR introduces 'scientific imagination' and apperception to probe students' understanding of previously learned linguistic concepts. Anticipating diverse student responses, DDR ensures TEFL Methodology learning objectives are met. The study also examines the emerging 'needs analysis' trend, emphasizing student-centered learning's role in fostering didactic creativity and enhancing TEFL Methodology instruction. Cases and Team Work diversify didactic creativity, yielding contextually relevant instructional designs. The research seeks to shift TEFL Methodology learning towards fostering innovative conditions that empower students in reflective, self-directed learning, thereby enhancing TEFL knowledge and practical skills mastery.